2019
DOI: 10.14740/gr1229
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Gastrojejunostomy for Superior Mesenteric Artery Syndrome Using Magnetic Compression Anastomosis

Abstract: An 89-year-old woman who was bedridden suffered repeated vomiting due to superior mesenteric artery syndrome (SMAS). We performed gastrojejunostomy via the magnetic compression anastomosis (MCA) technique because her situation was not improved by conservative therapy and because the operative risk was high. We prepared two neodymium magnets: a flat plate-shaped magnet (15 × 3 mm) and a ring-shaped magnet of the same size. The ring-shaped magnet which passed through a guidewire was pushed to the duodenum by an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
(17 reference statements)
1
1
0
Order By: Relevance
“…One case involved anastomotic obstruction after subtotal gastrectomy, and the other involved endoscopic gastrojejunostomy for superior mesenteric artery syndrome. In those reports, the magnets measured 15 × 3 mm, and the duration until creation of complete anastomosis was 10 days each, similar to our case [ 14 , 15 ].…”
Section: Discussionsupporting
confidence: 84%
“…One case involved anastomotic obstruction after subtotal gastrectomy, and the other involved endoscopic gastrojejunostomy for superior mesenteric artery syndrome. In those reports, the magnets measured 15 × 3 mm, and the duration until creation of complete anastomosis was 10 days each, similar to our case [ 14 , 15 ].…”
Section: Discussionsupporting
confidence: 84%
“…However, the study was halted prematurely due to a severe adverse event (stent perforation resulting in patient death). Subsequently, Kawabata et al 62 . considered the risk of serious complications associated with stent placement and suggested that balloon dilation should be performed in the presence of symptomatic anastomotic stenosis, instead of stent placement.…”
Section: Results For Mcamentioning
confidence: 99%
“…Laparoscopic approach has been reported to shorten post-operative length of hospital stay[ 129 , 142 ]. Most recently, a new technique of endoscopic gastrojejunostomy (so called lumen-apposing metal stent) has also been reported in several case reports as a safe and effective therapeutic option[ 146 - 148 ].…”
Section: Treatmentsmentioning
confidence: 99%